NDVI Based Vegetation Dynamics in Jember Regency from 2019 to 2024 Using Multitemporal Landsat 8 Imagery - Eris, Igor; Rambe, Syavitri Sukma Utami; Wahyuningtiyas, Loetvy (Universitas Pendidikan Nasional, 2025)
Vegetation dynamics in Jember Regency serve as a crucial indicator of environmental conditions influenced by anthropogenic factors. As a region where the agriculture and forestry sectors play a vital role in the local economy, contributing 25.71% to the Gross Regional Domestic Product (GRDP), monitoring vegetation change is highly important. This study aims to analyze temporal vegetation change in Jember Regency from 2019 to 2024 using Landsat 8 OLI/TIRS imagery processed on the Google Earth Engine cloud computing platform. The methods employed included calculating Normalized Difference Vegetation Index (NDVI), classifying vegetation change hierarchy using the Natural Breaks (Jenks) method, and conducting zonal statistical analysis to compare vegetation density trends between urban and rural areas of Jember Regency. This research revealed a disparity in vegetation density change between rural and urban areas (Patrang, Kaliwates, and Sumbersari Sub-Districts). Urban areas of Jember experienced degradation, with the mean NDVI value decreasing by 8% per year, from 0.500 in 2020 to 0.460 in 2024, indicating the conversion of agricultural/vegetated land into built-up areas. In contrast, rural areas were determined to be relatively stable, with NDVI mean value ranging from 0.584 to o.554 during the same period. Zonal analysis of the vegetation change map showed that more than 12,000 hectares of land underwent vegetation degradation, predominantly in urban areas of Jember Regency. Meanwhile, rural areas around Mount Gambir exhibited stability or increased vegetation density due to sustainable plantation management. These findings provide quantitative evidence of the impact of urbanization on environmental sustainability and emphasize the need for policies that balance development with the conservation of vegetated land to maintain ecological integrity and support the local economic and ecosystem sustainability of Jember Regency.